Curcumin as Efflux Pump Inhibitor Agent for Enhancement Treatment Against Multidrug Resistant Pseudomonas aeruginosa Isolates - Sulaiman, Sulaiman D.; Abdulhasan, Ghusoon A. (Iraqi Journal of Science, 2020)
Pseudomonas aeruginosa is considered as a developing opportunistic nosocomial pathogen and is well-known for its multidrug resistance that can be efficiently treated by a combination of antibiotics andefflux pump inhibitors (EPI). Therefore, the purpose of this study was to investigate the effect of curcumin as an EPI for the enhancement of the effectiveness of antibiotics against multidrug resistant (MDR) isolates ofP. aeruginosa. Susceptibility patterns of suspected bacteria was determined using the disc diffusion method andresistant bacteria were identified using chromogenic agar and 16S rDNA. The effectsof curcuminon the enhancement of antibiotics’s activity was evaluated usingthe broth microdilution method.The susceptibility patterns for 50 (67.6%) suspectedP. aeruginosaisolates showed that 36 (72%) of these isolateswere resistant to one of the used antibiotics,whereasonly 21 (42%) were MDR. The highest percentage of resistance was observedtoceftazidime (66%) followed by ciprofloxacin and levofloxacin (40%). Only 35 isolates were specified by chromogenic agar and 16S rDNAas P. aeruginosa.The minimal inhibitory concentration (MIC) of 35 isolates for ciprofloxacin resistant was between 4 and128 µg/ml while for ceftazidime was between 64and 512 µg/ml. After the addition of 50 μg/ml curcumin with ciprofloxacin, there wasa significant increase in the sensitivity (p≤ 0.01) of 13 MDR P.aeroginosa isolates whereas no differences in the sensitivity to ceftazidime were recorded before and after addition ofcurcumin. In conclusion, the results of this study show that curcumin can decrease the MIC value of ciprofloxacin in MDR isolates of P. aeruginosaand can be used as a native compound to enhance the treatment of resistant isolates with ciprofloxacin.